Respostas
respondido por:
0
teorema de Pitágoras
6^2+x^2=10^2
36+x^2=100
x^2=100-36
x^2=64
x=√64
x=8
o outro cateto mede 8 cm.
6^2+x^2=10^2
36+x^2=100
x^2=100-36
x^2=64
x=√64
x=8
o outro cateto mede 8 cm.
respondido por:
0
Usando o teorema de Pitágoras:
a²=b²+c²
a= hipotenusa, b e c são os catetos.
a=10
b=6
c=?
Substituindo:
10²=6²+c²
100=36+c²
100-36=c²
c²=64
c=
c=8 cm
a²=b²+c²
a= hipotenusa, b e c são os catetos.
a=10
b=6
c=?
Substituindo:
10²=6²+c²
100=36+c²
100-36=c²
c²=64
c=
c=8 cm
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás